Constraint-Based Concurrency and Beyond - Ueda, Kazunori (Electronic notes in theoretical computer science, 2006)
Constraint-based concurrency is a simple and elegant formalism of concurrency with monotonic mobile channels, whose history started in early 1980's as a subfield of logic programming. Although it has hardly been recognized as process calculi, there is a close connection between them. In this paper we try to convey the essence of constraint-based concurrency to the process calculi community. We also describe how it smoothly evolved into LMNtal (pronounced “elemental”), a language model based on hierarchical graph rewriting.